Evidence for Facial Nerve–Independent Mechanisms of Blinking in the Rat - Heaton, James T. (Association for Research in Vision and Ophthalmology, Inc., 2010)
PURPOSE. The rat facial nerve (CN VII) controls the orbicularis oculi (OO) muscle, which contracts to close the palpebral fissure during blinking. It was recently observed that rats are able to achieve nearly complete eye closure shortly after CN VII lesion, and hypothesized that the retractor bulbi (RB) muscle assumes an important compensatory role after CN VII lesion. This study was undertaken to determine the maintenance of rat corneal health and eye closure capability after lesion of the OO, RB, or both. METHODS. Twenty-two rats underwent RB transection; 12 of them had undergone complete unilateral CN VII transection (OO denervation) 15 weeks earlier. Corneal appearance and ability to blink in response to a corneal air puff was monitored weekly for 9 weeks. An additional 13 rats received CN VII transection and were video recorded (1000 frames/s) during elicited blinks at days 1, 3, 5/6, and 11 after surgery. RESULTS. Rats achieved nearly full or full eye closure after OO paralysis or RB myotomy, respectively. Ninety-two percent of rats maintained good corneal health after OO denervation over 9 weeks, consistent with compensatory eyelid movement served by the RB muscles. In contrast, only 40% of rats with loss of RB function alone and only 17% of rats with concurrent OO and RB paralysis were able to maintain corneal health by week 3. CONCLUSIONS. Like other small mammals, the rat RB musculature can support nearly complete eye closure when CN VII is lesioned, and must be carefully considered when using blink as a functional recovery parameter of facial nerve lesion.